An investigation of the relationship between bulk composition, inferred reaction progress and fluid-flow parameters for layered micaceous carbonates from Maine, USA - Evans, Katy; Bickle, M. (Blackwell Publishing, 2005)
Reaction progress exhibited by multivariant assemblages in micaceous limestones can provide an excellent record of metamorphic fluid flow. However, it is necessary to understand the sensitivity of these assemblages to bulk-composition parameters. Here, analysis of bulk composition on different scales and pseudosection construction are used to draw conclusions on relationships between bulk composition, fluid flow and reaction progress. Issues addressed include the effects of bulk composition on the mineralogical evolution of micaceous carbonates, the sensitivity of bulk composition to bulk composition sampling methods, the magnitude of cross-layer fluid-composition gradients, the potential for metasomatism to drive reaction progress, and the relative timing of reaction in adjacent layers. Pseudosections successfully represent observed mineral assemblages, constrain the position of reactions in T-X(CO2) space, and allow assessment of the sensitivity of reaction position, inferred reaction progress and calculated fluid fluxes to uncertainties in bulk composition. The scale of bulk-composition sampling affects bulk compositions, calculated modes, predicted mineral assemblages and calculated fluid compositions. Larger samples record an average of different lithological subdomains, while pointcount-derived bulk compositions are subject to uncertainties related to the small number of sample points. The optimum bulk composition for pseudo section purposes probably lies between measured bulk compositions. Results suggest that reaction progress in some extensively reacted layers was driven by infiltration of H2O-rich fluid which flowed or diffused parallel to layering, perpendicular to layering in response to fluid-composition gradients, and out of veins. Small variations in fluid composition across layering (X(CO2) <0.02) were maintained by internal buffering by the mineral assemblages. Internal buffering must also have driven samples up a sequence of narrow low-variance fields in T-X(CO2) space,and so reaction in adjacent layers must have close to simultaneous. Metasomatic effects on reaction progress are likely to have been small, so long as the porosity was low.